27th International Conference on Distributed Computing Systems (ICDCS '07) 2007
DOI: 10.1109/icdcs.2007.109
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Symbolic Techniques in Automated Synthesis of Distributed Programs with Large State Space

Abstract: Automated formal analysis methods such as program verification and synthesis algorithms often suffer from time complexity of their decision procedures and also high space complexity known as the state explosion problem. Symbolic techniques, in which elements of a problem are represented by Boolean formulae, are desirable in the sense that they often remedy the state explosion problem and time complexity of decision procedures. Although symbolic techniques have successfully been used in program verification, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 15 publications
0
67
0
Order By: Relevance
“…In particular, in [Bonakdarpour and Kulkarni 2007], we have shown that symbolic techniques can be used to effectively synthesize distributed programs with the size of reachable states exceeding 2 100 . We, therefore, expect that these approaches would also assist significantly in managing state space during the addition of UNITY properties.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in [Bonakdarpour and Kulkarni 2007], we have shown that symbolic techniques can be used to effectively synthesize distributed programs with the size of reachable states exceeding 2 100 . We, therefore, expect that these approaches would also assist significantly in managing state space during the addition of UNITY properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, some transitions cannot be removed (like the uncontrollable transitions in DCS), but this is the case only of fault transitions (while in DCS, any event can be uncontrollable, not only faults). An efficient BDD-based algorithm has been presented in [8] and implemented in the SYCRAFT tool [10]. 8 Attie et al have also proposed an automatic synthesis method for fault tolerant programs [3].…”
Section: Related Workmentioning
confidence: 99%
“…An efficient BDD-based algorithm has been presented in [8] and implemented in the SYCRAFT tool [10]. 8 Attie et al have also proposed an automatic synthesis method for fault tolerant programs [3]. In their approach, a system is a set of concurrent processes, each consisting of a directed graph, where states are connected by transitions labeled by guarded commands.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is orthogonal to that in [3] in that this work can be extended in the context of dealing with probabilities and their work can be extended to deal with addition of graceful degradation. Algorithms for automatic addition of faulttolerance [1], [6] add fault-tolerance concerns to existing untimed or real-time programs in the presence of faults, and guarantee the addition of no new behaviors to the original program in the absence of faults. In the context of this paper, we utilize the synthesis algorithm for adding fault-tolerance.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the existing approaches for automated addition of fault-tolerance include [1]- [3], where three different levels of fault-tolerance, namely nonmasking, masking and stabilizing, are considered. In all these levels, if the fault perturbs the program then it is guaranteed to recover to legitimate states from where it satisfies its specification.…”
Section: Introductionmentioning
confidence: 99%